Comparison of two pain scales: Behavioral pain scale and critical-care pain observation tool during invasive and noninvasive procedures in intensive care unit-admitted patients - Shiva Gomarverdi; Ladan Sedighie; Mohamad Ali Seifrabiei; Mahshid Nikooseresht (Wolters Kluwer Medknow Publications, 2019)
Background: Critically ill patients admitted to intensive care units (ICUs) frequently experience pain, but the severity of pain in this group of patients is underestimated by the treatment team due to barriers to verbal communication. The aim of the present study was comparing the severity of pain measured by two scales: behavioral pain scale (BPS) and critical-care pain observation tool (CPOT) in ICU-admitted patients during routine daily procedures. Materials and Methods: Ninety patients were enrolled in the study. The severity of pain was measured during resting, invasive (suctioning) and noninvasive (mouthwash and body position change) procedures, and respiratory physiotherapy with two scales: BPS and CPOT. Wilcoxon and Friedman statistical tests were used to compare the score of pain in different situations, and Spearman correlation coefficient was also used to measure the correlation of pain score measured by two scales. Results: Patients experienced no pain during resting, mild pain during changing position, and respiratory physiotherapy, mild-to-moderate pain during mouthwash and moderate pain during secretion suctioning. Wilcoxon test used for pairwise comparisons between pain score in different situations showed a significant difference in both scales (p < 0.05). There were positive and strong correlations (r > 0.80, p < 0.05) between the pain score measured by BPS and CPOT from ICU-admitted patients in all procedures. Conclusions: Critically ill patients in ICU experience a different range of pain in routine daily care. BPS and CPOT scales could be used successfully for monitoring of pain in this group of patients.